2018
DOI: 10.1007/s00134-018-5268-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen colonization of the gastrointestinal microbiome at intensive care unit admission and risk for subsequent death or infection

Abstract: Enterococcus status at ICU admission was associated with risk for death or all-cause infection, and rectal carriage of common ICU pathogens predicted specific infections. The gastrointestinal microbiome may have a role in risk stratification and early diagnosis of ICU infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
143
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 154 publications
(150 citation statements)
references
References 39 publications
7
143
0
Order By: Relevance
“…An untargeted hierarchical linear discriminant analysis (LDA) effect size algorithm (LEfSe) was used with sequencing results to identify altered taxa based on fiber intake. Additionally, Enterococcus relative abundance was prespecified as a secondary outcome of interest within the gastrointestinal microbiome because our previous study identified it as an independent predictor of death and infection in the ICU study . Standard microbiome α diversity measures (Shannon and Chao index) were assessed also based on 16S rRNA gene sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An untargeted hierarchical linear discriminant analysis (LDA) effect size algorithm (LEfSe) was used with sequencing results to identify altered taxa based on fiber intake. Additionally, Enterococcus relative abundance was prespecified as a secondary outcome of interest within the gastrointestinal microbiome because our previous study identified it as an independent predictor of death and infection in the ICU study . Standard microbiome α diversity measures (Shannon and Chao index) were assessed also based on 16S rRNA gene sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…In bone marrow transplant recipients and selective ICU cohorts, increased abundance of SCFA‐producing bacteria was associated with decreased MDR organism colonization, including decreased vancomycin‐resistant Enterococcus (VRE) . In the ICU, diminished levels of SCFA producers have been associated with higher Enterococcus and risk for death . In healthy volunteers and ambulatory patients, fiber is well tolerated and increases SCFA producer levels …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is possible that the microbiota profiles in these patients serve as surrogate markers of critical illness, emerging evidence also shows that the microbiota can conversely influence disease activity. In a prospective study of 301 patients in the medical ICU, the presence of Enterococcus in the stool at the time of admission was associated with all‐cause infection or death . Rectal carriage of certain organisms ( Enterococcus , Escherichia coli , C. difficile , Pseudomonas , and Klebsiella ) was also associated with subsequent extraintestinal culture–proven infection with the same organism.…”
Section: Introductionmentioning
confidence: 99%
“…The paper by Freedberg et al [16] in this issue of Intensive Care Medicine provides novel insights to appraise how the characteristics of the gut microbiota upon ICU admission may predict death or subsequent infection in critically ill patients. A total of 301 patients were prospectively included in this single-ICU study.…”
mentioning
confidence: 99%